PENINGKATAN KESADARAN KESEHATAN DAN KETERAMPILAN KREATIF MELALUI KEGIATAN POSYANDU REMAJA: PENYULUHAN, PEMERIKSAAN KESEHATAN, DAN PELATIHAN ECOPRINT - Amanda Adisty; Yanti Nopita; Azizah; Desti Anggraini; Dheyani Mustika Putri; Viora Antasya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to evaluate the nutritional status of adolescents in Harau District, Lima Puluh Kota Regency, using measurements of body weight, height, blood pressure, as well as upper arm circumference (LILA) and waist circumference. The sample consisted of adolescents aged 10-18 years participating in Posyandu Remaja activities. Data obtained were analyzed descriptively to determine the variations in adolescent nutritional status and the relationship between body measurements and the potential risk of obesity and malnutrition. The results showed significant variations in adolescent nutritional status, with some adolescents experiencing malnutrition and others at risk of obesity. LILA and waist circumference measurements proved effective in assessing adolescent nutritional status more objectively. The Posyandu Remaja program plays an important role in increasing adolescents' health awareness, particularly regarding healthy eating habits and the importance of physical activity. Based on these findings, it is recommended to continuously enhance nutritional monitoring of adolescents and involve families and schools in supporting healthy lifestyles to prevent the risk of non-communicable diseases in the future.